Utilization of Coffee Peel Waste as Biosorbent for Rhodamine B Dye Removal: Isotherm, Kinetics, and Thermodynamic Studies - Zein, Rahmiana; Prestica, Yona; Deswati; Ramadhani, Putri (Indonesian Journal of Environmental Management and Sustainability, 2025)
Coffee Peel Waste (CPW) is an abundant and inexpensive material that can be employed as a biosorbent to remove Rhodamine B (RB) dye from wastewater. This research utilized the batch adsorption approach to optimize the parameters of pH, starting concentration of dye and period of contact. At pH 8, 1000 mg/L as the starting concentration and 105 minutes as the contact time, the optimal conditions were established, exhibited an adsorption capacity of 71.8454 mg/g, aligning with the Langmuir isotherm model, wherein mechanism of adsorption demonstrated monolayer adsorption, and was most appropriate for the kinetic model of pseudo-second order. Thermodynamic analysis revealed that the adsorption occurred spontaneously and released heat, confirming its exothermic nature. FTIR characterization identified the functional sites involved in the adsorption mechanism. At the same time, SEM-EDX analysis showed morphological changes and an increase in some aspects after adsorption, confirming the attachment of RB to the surface of the CPW. This study reveals the advantages of CPW as an innovative, efficient and sustainable biosorbent, offering a new solution in wastewater treatment based on agro-industrial waste.